Enhancement of energy efficiency and sustainability through green building index platinum certification in Malaysian building design - Billy Kee Haan Sia; Mohd Aifaa Mohd Ariff (Majlesi Journal of Electrical Engineering)
This paper presents a comprehensive study on enhancing energy efficiency (EE) and sustainability in building design, focusing on implementing the Green Building Index (GBI) Platinum standards for a proposed office development in Malaysia. While international green building standards, such as LEED, BREEAM, and Green Star, offer robust frameworks, they often fail to address Malaysia’s  tropical climate challenges. The GBI framework bridges this gap by tailoring its criteria to local environmental, social, and economic  conditions. This study emphasizes advanced commissioning processes, renewable energy integration, and sustainable maintenance practices, including calculations of U-values, Overall Thermal Transfer Value (OTTV), Total Building Energy Consumption (TBEC), and Building Energy Intensity (BEI) through simulations and optimizations. Results show significant improvements, including OTTV reduced to 39.48 W/m2, TBEC reduced by over 65%, and BEI decreased by 66% compared to baseline designs. GBI Platinum  certification yields higher annual savings and a longer payback period compared to MS1525:2007, with benefits validated through a 4.08-year payback period. This study provides a valuable framework for sustainable building development by addressing Malaysia’s climatic challenges and leveraging innovative EE strategies.